2021
DOI: 10.1080/19490976.2021.1884514
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the factors influencing microbial colonization of the preterm infant gut

Abstract: Prematurity coupled with the necessary clinical management of preterm (PT) infants introduces multiple factors that can interfere with microbial colonization. This study aimed to review the perinatal, physiological, pharmacological, dietary, and environmental factors associated with gut microbiota of PT infants. A total of 587 articles were retrieved from a search of multiple databases. Sixty studies were included in the review after removing duplicates and articles that did not meet the inclusion criteria. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 132 publications
(293 reference statements)
6
70
0
Order By: Relevance
“…These results have together indicated that habitat ltering, i.e., variables that shape the intestinal environment, is a dominant driver of infant microbiome succession. Other studies have additionally shown that delivery mode shapes the initial colonizers of the infant gastrointestinal tract [62,76], which includes faecal microbes for vaginally delivered infants, such as Bacteroidota [78,79] complementing our study, and skin microbes for Caesarean-section infants. However, infants delivered at term possess an advantage as they can access the home environment usually relatively quickly, whereas preterm infants usually remain in the hospital environment at length with sanitation protocols preventing normal microbial dissemination [80].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…These results have together indicated that habitat ltering, i.e., variables that shape the intestinal environment, is a dominant driver of infant microbiome succession. Other studies have additionally shown that delivery mode shapes the initial colonizers of the infant gastrointestinal tract [62,76], which includes faecal microbes for vaginally delivered infants, such as Bacteroidota [78,79] complementing our study, and skin microbes for Caesarean-section infants. However, infants delivered at term possess an advantage as they can access the home environment usually relatively quickly, whereas preterm infants usually remain in the hospital environment at length with sanitation protocols preventing normal microbial dissemination [80].…”
Section: Discussionsupporting
confidence: 69%
“…Diet and antibiotics are known to have a large impact on the infant microbiome, exceeding stochasticity [33,62,76]. Further, a seminal study by Feng and colleagues has demonstrated that the in uence of relative microbial tness on infant microbiome succession appears to supersede historical contingency, i.e., the order of introduction of microbes [77].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at 1 week of age, the gut microbiota of neonates delivered by cesarean section is characterized by high levels of Clostridium, but not Bifidobacterium and Bacteroides, compared with that of infants delivered by spontaneous vaginal delivery (13,16). Meanwhile, antimicrobial agents often reduce gut bacterial diversity and disrupt the ecological balance of the neonatal microbiome (12,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%